Progesterone decreased indoleamine 2,3-dioxygenase 1(IDO1) expression in early pregnancy chorionic villi and decidua - Minyan Yang; Guanyou Huang; Hua Qian; Jun Wang; Shuyun Zhao; Shixiang Li; Yan Yuan (Taylor & Francis Group, 2021)
Indoleamine 2,3-dioxygenase1(IDO1) is one of the most important proteins in protect the embryos from the mother's immune system during pregnancy. However, the regulation of the protein expression at the maternal-foetal interface is not fully known. We aimed to study the regulation of IDO1 expression by progesterone in villi and decidua of in early pregnancy. Fifty cases of early pregnancy women's villi and decidua were collected. Tissue explants of chorionic villi and the decidua were cultured in media containing in different concentrations of progesterone, in the presence or absence of mifepristone. Western blot analysis and immunofluorescence were used to detect the expression of IDO1 in chorionic villi and decidua in cultured tissues. IDO1 protein was identified in chorionic villi and decidua tissues of normal pregnant women, and the expression of IDO1in the decidua was significantly higher than those in chorionic villi. Progesterone decreased IDO1 expression in early pregnancy chorionic villi and decidua, and mifepristone, as the progesterone inhibitor, reverted this effect. In normal physiological state of pregnancy, progesterone may be involved in the regulation of immune tolerance by negative regulation of IDO1 expression at maternal foetal interface. Progesterone may down-regulate IDO1 expression during early pregnancy.